EFFECTIVENESS OF HYPNOTHERAPY IN REDUCING ANXIETY AND BLOOD PRESSURE AMONG WOMEN WITH GESTATIONAL HYPERTENSION - Evi Zahara; Nurlaili Ramli; Pepi Hapitria; Anita; Nanda Norisa (International Archives of Medical Sciences and Public Health, 2026)
Gestational hypertension (GH) is a common pregnancy complication associated with adverse maternal and fetal outcomes and is often accompanied by anxiety, which may be associated with elevated blood pressure. This study examined the association between participation in a hypnotherapy program and changes in blood pressure, anxiety, and gestational duration among pregnant women with GH. A quasi-experimental pre-test–post-test control group study was conducted among 50 pregnant women with gestational hypertension in Aceh Barat Regency, Indonesia. Participants were recruited using purposive sampling and allocated through a non-random procedure to an intervention group (n = 25), which received structured hypnotherapy in addition to standard antenatal care, or a control group (n = 25), which received standard antenatal care alone. Anxiety was assessed using the Hamilton Anxiety Rating Scale (HARS), while systolic and diastolic blood pressure were measured before and after the intervention. Continuous outcome measures were analyzed using the Wilcoxon signed-rank test for within-group comparisons and the Mann Whitney U test for between-group comparisons. The intervention group demonstrated significantly greater reductions in systolic and diastolic blood pressure and HARS anxiety scores than the control group (*p* < 0.05). Although improvements in categorical blood pressure and anxiety status were observed in both groups, these descriptive findings did not reflect the magnitude of change captured by continuous measurements. No statistically significant between-group difference was found for gestational duration (*p* > 0.05). Participation in the hypnotherapy program was associated with greater improvements in blood pressure and anxiety than standard antenatal care alone.